2018
DOI: 10.24059/olj.v22i3.1464
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-Based Analysis of Student Success in Online Courses

Abstract: Online courses today give a broad, diverse population access to higher education. Despite postsecondary institutions embracing this opportunity, scholarly literature reveals persistent concern over low retention rates in online courses. In response to this concern, an explanatory sequential, mixed methods study was conducted in three phases at a public research university to simultaneously explore personal, circumstantial, and course variables associated with student success from a strengths-based perspective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
12
0
2
Order By: Relevance
“…Prior experience. Prior content knowledge, course format experience, or prior academic experience have been outlined as important for student success in both online (Blau et al, 2017;Estelami, 2014;Gering, Sheppard, Adams, Renes, & Morotti, 2018;Murph & Stewart, 2017) as well as in traditional face-to-face formats (Duff, 2004;Hailikari, Nevgi, & Komulainen, 2008;Martin, Wilson, Liem, & Ginns, 2013). Those who have successfully completed prior online courses evidence significantly higher course completion rates compared to students who have failed to complete a prior online course (Dupin-Bryant, 2004;Hachey et al, 2015).…”
Section: Racementioning
confidence: 99%
See 1 more Smart Citation
“…Prior experience. Prior content knowledge, course format experience, or prior academic experience have been outlined as important for student success in both online (Blau et al, 2017;Estelami, 2014;Gering, Sheppard, Adams, Renes, & Morotti, 2018;Murph & Stewart, 2017) as well as in traditional face-to-face formats (Duff, 2004;Hailikari, Nevgi, & Komulainen, 2008;Martin, Wilson, Liem, & Ginns, 2013). Those who have successfully completed prior online courses evidence significantly higher course completion rates compared to students who have failed to complete a prior online course (Dupin-Bryant, 2004;Hachey et al, 2015).…”
Section: Racementioning
confidence: 99%
“…Those who have successfully completed prior online courses evidence significantly higher course completion rates compared to students who have failed to complete a prior online course (Dupin-Bryant, 2004;Hachey et al, 2015). Moreover, students with higher academic standings (e.g., seniors) have been found to have higher success rates (Gering, Sheppard, Adams, Renes, & Morotti, 2018) as well as lower withdrawal rates (Cochran et al, 2014;Levy, 2007), with this finding holding across online and face-to-face formats (Yen et al, 2018). Students with limited academic experience (i.e., freshmen) exhibit higher D-grade/fail/withdraw (DFW) rates when taking a course online compared to faceto-face (Urtel, 2008).…”
Section: Racementioning
confidence: 99%
“…Online enrollments climbed between 2011 and 2016 while traditional on-campus enrollments decreased [18]. Online education, quite simply, continues to increase in popularity giving a broad and diverse population access to higher education; however, despite its growth, online education is plagued by low retention rates [19]. At the course level, studies have consistently found online course completion rates to be much lower than the rates for face-to-face courses [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A three phase study that looked at the enrollments across four years in online courses then gave an assessment of perception and noncognitive attributes to a sample of 257 students, and conducted personal interviews with a subset of 12 students who had completed the initial survey and assessment. They found that noncognitive factors such as the ability to teach one's self, student initiative, and time management were significant factors in online student success [19]. Doctoral studies requires tremendous persistence as they are based on the achievement of a long-term goal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead of simply shrugging our shoulders and bemoaning the loss of these interactions due to COVID-19, the burden is on faculty to create opportunities for connection with students in our online classes. Research shows that the instructor is more important than any other aspect of an online course (Muljana and Luo 2019;Nistor and Neubauer 2010) and the quality of faculty-student interactions consistently predicts online retention and success (Gering et al 2018;Jaggars and Xu 2016).…”
Section: Making Human Connections In Online Teachingmentioning
confidence: 99%